Strategi Peningkatan Engagement Melalui Produksi Konten dan Preferensi Audiens - Fikriyah, Siti Hailatul; Sulistyo, Ponco Budi; Tomohardjo, Irmulansati (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Digital media development has encouraged Sasmita Jaya Foundation to utilize it as an information and marketing medium by using SJ TV YouTube channel which presents various content, but faces challenges in increasing audience engagement. Study aims to determine the strategy for increasing engagement through content production and audience preferences using the SOME model and audience engagement. Research approach is qualitative with a case study method. Data were collected through observation, documentation, and interviews with informants from Head and Production Division of SJ TV, practitioners and academics as content creators, subscriber and viewer of SJ TV. Results of study show the content type, upload consistency, and suitability with audience preferences are implemented to increase engagement. Share strategy has been proven to be a determinant of content success. Optimize strategy is data based approach and effective trend analysis that increases engagement. Manage strategy shows professional and structured internal management. Engage strategy has succeeded in creating active audience engagement. Audience engagement through content engagement is carried out by compiling relevant content, educational value, and touching emotional aspects of audience. Audience engagement through media engagement presents a responsive and interesting viewing experience. Audience engagement through engagement marketing activities has succeeded in increasing engagement significantly.